Influence of Dental Health Against Knowledge and Attitude of Elementary School Students on Dental Caries in the Sunter Jaya Jakarta Utara - Shaharani, Yessie; Setiaji, Bambang (Journal of Ultimate Public Health, 2018)
Background, Dental health problems in Indonesia to date still need to get attention considering the high prevalence of dental caries. From the survey results of DKI province 2015, shows only 14% of children aged 5-6 years free of caries. Knowledge and sikaf about oral health will indirectly maintain oral health and ultimately can prevent the occurrence of dental caries. This means that knowledge about school age is the age of children between 6-12 years old teeth and mouth can affect the incidence of dental caries. Children entering school age have a higher risk of caries. Mothers need to keep an eye on children's snack patterns at school. SDN 01 Sunter Jaya has high caries data compared to other SDNs ie DMF-T index of 4.0.Methods,  The purpose of this study was to know the influence of dental health education on the knowledge and attitude of elementary school students about dental caries in Sunter Jaya area, North Jakarta. This research used quasi experimental approach model, with Pretest Posttest With control group design where the researcher made the first observation (pretest) done before dental and oral health counseling. The place of research is at SDN 01 Sunter Jaya which is located at Sunter Jaya Jakarta Utara. The reseacrh start on May - November 2017. The sample in this study for the experimental group and control group are 36 students each.Results, After counseling students have a good knowledge of 24 students (66.7%) and 32 students (88.9%) and students who are positive about dental and oral health. The result of statistical test shows that there is a significant difference between the knowledge and the students' attitude before and after being given health counseling value p value 0,000 ≤ α 0,05. From the group multivariate GLM outcomes given extension both to improve the knowledge and attitude of students (p value = 0,000) and the value of each knowledge and attitude of students 33,056 and 12,722.Conclusion There is a significant influence between dental and oral health information on students' knowledge and attitude about dental caries at SDN 01 Sunter Jaya students. Suggestions for SD 01, Pukesmas, and Sudinkes always prioritize dental and oral hygiene and hygiene with counseling and improve the UKGS program in schools.